2010
DOI: 10.1299/jsdd.4.103
|View full text |Cite
|
Sign up to set email alerts
|

Bang-bang Type Semi-active Control of Civil Structures: A Prediction-based Approach

Abstract: We propose a semi-active control of civil structures based on a one-step-ahead prediction of the seismic response. The vibration control device (VCD), which has been developed by authors, generates two types of resistance forces, i.e., a damping force proportional to the relative velocity and an inertial force proportional to the relative acceleration between two stories. The damping coefficient of the VCD can be changed with a command signal to an electric circuit connected to the VCD. In the present paper th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…This paper presents an electromagnetic inertial mass damper (EIMD) that combines an electromagnetic damper and an IMD into one device [14][15][16][17][18][19][20]. Electromagnetic dampers have been developed for automobile suspensions [21] and a damping device for a structure [22].…”
Section: Introductionmentioning
confidence: 99%
“…This paper presents an electromagnetic inertial mass damper (EIMD) that combines an electromagnetic damper and an IMD into one device [14][15][16][17][18][19][20]. Electromagnetic dampers have been developed for automobile suspensions [21] and a damping device for a structure [22].…”
Section: Introductionmentioning
confidence: 99%
“…In the premise of the predictive semi‐active control law , design parameters in the model for the control system design and the semi‐active control law are simultaneously optimized with the GA. With the simulation study, the semi‐active control system obtained with the present methodology is shown to achieve the better control performance compared with not only the NC and Pon cases but also two semi‐active control cases where the detailed dynamic characteristics of the structural system is exactly known.…”
Section: Resultsmentioning
confidence: 99%
“…With the energy dissipative property that is inherent in general semi-active control systems, the simultaneous optimal design problem of the model for the control system design and the model-based semi-active control law is formulated without the stability constraint of the control system. In the premise of the predictive semi-active control law [9], design parameters in the model for the control system design and the semi-active control law are simultaneously optimized with the GA. With the simulation study, the semi-active control system obtained with the present methodology is shown to achieve the better control performance compared with not only the NC and Pon cases but also two semi-active control cases where the detailed dynamic characteristics of the structural system is exactly known.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations